2001
DOI: 10.1097/00004770-200103000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Anti–Inflammatory Effects of Human Recombinant Copper–Zinc Superoxide Dismutase on Pulp Inflammation

Abstract: Inflammation in the dental pulp is accompanied by release of a wide variety of highly oxidative molecules known as reactive oxygen species (ROS). ROS concentrations are controlled in vivo by an antioxidant enzyme scavenger system that may be overwhelmed by the increases in ROS production seen during inflammation. Supplementation of the antioxidant defense system, therefore, may limit the severity of the inflammatory response to injury due to this component. To test this hypothesis, this study examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 16 publications
4
23
0
2
Order By: Relevance
“…Indeed, several lines of evidence indicate that persistent or chronic pulpal inflammation overrides repair processes and the currently accepted paradigm is that regenerative processes follow only after resolution of infection and inflammation. [79][80][81] In support of this, our data combined with that from other studies indicate that cytokines and growth factors, such as TNF-a and TGF-b as well as released dentine matrix components, which are present at relatively high levels during the infectious and inflammatory processes, have deleterious effects on pulpal tissue and can induce cellular death. 56,70,82,83 It is also interesting that studies using stem cells, including those derived from the dental pulp, have demonstrated that binding of their TLRs results in activation of the NF-kB pro-inflammatory signaling cascade, which can result in inhibition and obstruction of the differentiation processes.…”
supporting
confidence: 85%
“…Indeed, several lines of evidence indicate that persistent or chronic pulpal inflammation overrides repair processes and the currently accepted paradigm is that regenerative processes follow only after resolution of infection and inflammation. [79][80][81] In support of this, our data combined with that from other studies indicate that cytokines and growth factors, such as TNF-a and TGF-b as well as released dentine matrix components, which are present at relatively high levels during the infectious and inflammatory processes, have deleterious effects on pulpal tissue and can induce cellular death. 56,70,82,83 It is also interesting that studies using stem cells, including those derived from the dental pulp, have demonstrated that binding of their TLRs results in activation of the NF-kB pro-inflammatory signaling cascade, which can result in inhibition and obstruction of the differentiation processes.…”
supporting
confidence: 85%
“…Dentin bonding agents may present different cytotoxicity by the interaction of the multiple components, thus the determination of the cytotoxicity of the product instead of the monomer is significant 3,8) . The increased reactive oxygen species (ROS) have been reported as responsible for the cytotoxic effects of the resin-based dental materials [9][10][11] . Cells try to overcome with monomer-induced oxidative stress by expression of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The St electrode generated higher amounts of alkoxyl radical than the Ni-Ti electrode. Free radicals are involved in inflammatory reactions in both pulp and periapical lesions (16,17) and antioxidants may play important roles in the regulation of inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%